The effects of aflatoxin and gluconıannan on some hematological parameters in rabbits - Nurcan Dönmez; Banu Atalay; Deniz Fedai (Eurasian Journal of Veterinary Sciences)
The aim of this study was to evaluate the effects of aflatoxin and glukomannan on some hematological parameters. In the study, 40 New Zelland rabbits were used and the rabbits were seperated equally to four groups as control (K), glucomannan (G), glucomannan+ aflatoksin (AF) and aflatoxin (A). At the end of the (10 week) experiment, erythrocyte and haemoglobin levels decreased significantly (p<0.05) in A and AG groups compared with control group and there was no differences in MCV, MCH and MCHC levels between groups. When compared with control leukocyte count increased in A and AG groups (p<0.05). Additionally, heterofil count was higher and lymphocyte count was lower in A group (p<0.05) than control. In conclusion, the results determined in the study might be important to demonstrate the effects cf aflatoxicosis and glucomannan on some haematological parameters before the clinical symptoms appear.